Pemberdayaan Masyarakat Melalui Edukasi dan Praktik Pembuatan Teh Herbal Daun Salam (Syzygium Polyanthum) untuk Peningkatan Kesehatan - Adi Lukman Hakim; Ganda Puji Adzhar Muttaqin; Yusrotul Ulya; Yuni Furoida Maknuna; Yohana Ayu Agustine; Meiliya Widati; Avivatul Fitri Ulwiyyah (Jurnal Medika: Medika, 2025)
This study examines the use of bay leaves (Syzygium polyanthum) as a base ingredient for herbal tea in an effort to improve public health in Garung Village, Sambeng Subdistrict, Lamongan Regency. The programme was implemented through the 2025 Community Service Programme of Muhammadiyah University Lamongan, focusing on education about the benefits of bay leaves and the practice of making herbal tea. The main activities included health seminars and hands-on training in herbal tea production, involving local residents, particularly the PKK group and the elderly, as the primary target audience. Bay leaf tea was introduced not only as a traditional beverage but also as a healthy alternative drink with the potential to support modern lifestyles. Community enthusiasm was evident from the high level of participation in discussions and product-making practices. However, there were constraints in the form of limited tools and materials that hampered the optimisation of activities, necessitating sustainability strategies such as the procurement of simple equipment and more effective utilisation of local resources. The research results show that community empowerment through the use of traditional plants can increase health awareness and open up opportunities for the development of small herbal-based businesses. Overall, this programme has made a positive contribution to improving the quality of life of rural communities, strengthening local potential, and encouraging the creation of healthy lifestyles that can be developed sustainably.